UPAYA PENINGKATAN KEMAMPUAN KOGNITIF ANAK AUTIS DALAM MENGENAL KONSEP WARNA MELALUI PERMAINAN ALAT MUSIK ANGKLUNG - Nur Wahyuni (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2022)
The focus of this research is how the form of the implementation of the game using angklung media in recognizing the concept of color to improve aspects of the cognitive development of autistic children and how the results of applying the angklung musical instrument game method to the cognitive abilities of autistic children in KB Inclusion Angrek Mandiri. The method used is the Kemmis and Mc class action research cycle model. Tanggart. The subjects studied were autistic children in the Anggrek Mandiri KB Inclusion with a total of eight children. Data collection techniques through observation, interviews and documentation. The data analysis technique used in this research is descriptive qualitative and quantitative. The assessment instrument for observation activities is an observation sheet (checklist). The standard indicator of classical completeness in this study is 75% of the indicators achieved by children. The results showed that there was an increase in cognitive ability to recognize the concept of color in autistic children after practicing through the Angklung musical instrument. The results of observations in the pre-cycle that reached the completion criteria of 12.5% ​​then increased by 50% in the implementation of the first cycle and increased by 75% in the second cycle.